Kolaborasi Perpustakaan & Stakeholder - Purwani Istiana (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2016)
Resources which owned by library are limited. Libraries are not able to fully meet the expectations and desires of its users. Collaboration is a smart action for libraries and librarians to maximize their resources and overcome the limitations of existing resources. Practices of collaboration can be done either in the college library, school library and the public library. The collaboration is helpful to increase library services, the maximizing of resources are owned by the library. It spurs creativity and innovation opportunities. Need attitude and commitment of an individual to involve in the collaboration i.e a strong will to collaborate, creative and innovative, willing to continue to learn, and the ability to communicate. Collaboration is one of solution to increase library performance and quality.